Farmers' practices and soil and water conservation programs : summary proceedings of a workshop, 19-21 Jun. 1991, ICRISAT Center, India - Kerr, J. M. (Patancheru, Andhra Pradesh, India : International Crops Research Institute for the Semi-arid Tropics ; Morrilton, Ark., USA : Winrock International Institute for Agricultural Development, 1991)
Seminar papers.
Keywords: Agricultural conservation -- Congresses; Soil conservation projects -- Congresses; Water conservation projects -- Congresses; Watershed management -- Congresses